Sheikh Abdul Wahab Calau's Intellectual Practices: A Structuration Study in 19th-Century West Sumatra - Yudhi Andoni; Novi Yulia (Islam Transformatif : Journal of Islamic Studies, 2024)
This research examines the distinctive intellectual practices of Sheikh Abdul Wahab Calau at Surau Calau in Sijunjung during the mid-19th century. His contributions significantly enriched the intellectual landscape of Islam in Minangkabau, highlighting previously underexplored scholarly movements of the era. Employing historical methodologies—data collection, critical evaluation, classification, and historiographical analysis—this study contextualizes Calau (1830–1869) within his scholarly lineage, notably alongside Sheikh Burhanuddin Ulakan, a pivotal figure in the development of Tariga Syattariyah in the early 17th century. Calau's innovative pedagogical strategies reflected his personal experiences and adeptly mirrored and expanded the social structures of Surau Calau. Applying Giddens' structuration theory, this research vividly reveals the dynamic interplay between individual agency and social structures that facilitated intellectual transformation, keeping the audience engaged. Ultimately, Calau's authority derived from a robust scholarly genealogy, innovative teaching methods, and interpretative approaches to religious texts.